Vernacular Features in Rural Housing of the Aurassien massif between Traditional Practices and Bioclimatic Aspect. Case study of Ain Zaatout (Algeria) - Berbouche, Chafia; Sriti , Leila; Latreche, Sihem (Technium Social Sciences Journal, 2023)
The rural habitat in the Aures region is an excellent example on vernacular and human architecture. It reflects how inhabitants of this region responded to their requirements in an ingenious way and how local builders have succeeded to respond to challenges of climate, building materials and cultural expectations despite the particularly harsh environmental conditions of the Aures. The aim of this study is to determine the strategies used in vernacular constructions to deal with the severe climatic conditions that prevail in the Aures region. Precisely, rural dwellings in Ain Zaatout village (Beni Ferah) were studied to emphasize the importance of the architectural properties of the traditional houses in terms of thermal performance and climatic adaptability. In this regard, an extensive literature review was carried out on previous studies that investigated the Aures settlements. Accordingly, a comprehensive knowledge on typical Aurassien village and various data including spatial organisation, architectural characteristics and construction materials and techniques have been gathered. Based on this background, a qualitative analysis supported by field measurements was conducted. Then, two representative houses were selected as case studies for monitoring comfort parameters in summer period. Finally, the traditional and contemporary houses were compared in terms of their thermal performance. Through this study, the most frequently used strategies and their effectiveness were derived. The results indicate that vernacular rural habitat in the Aurassien villages is creatively adapted to the environmental conditions and uses various climate responsive strategies. The study additionally reveals that vernacular constructions in the Aures are more adapted to the climate constraints and social needs than contemporary residential buildings. These results were confirmed by hydrothermal values where main indoor temperature in a traditional rural house was less than external values by 3 °C and more humidified, while in modern house indoor temperature records were more than the exterior by 1°C. Thus, vernacular climatic responsive strategies must be considered as a reference for nowadays environmental issues in rural areas. Moreover, they can be feasible for contemporary buildings and, consequently, they could contribute greatly towards improving indoor thermal comfort whilst reducing buildings energy demand.